Sosialisasi Penggunaan Aplikasi (Sumiferos) Pencegahan Anemia dengan Kepatuhan Ibu Hamil Mengkonsumsi Tablet Besi - Rosmaria Manik (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The high incidence of anemia in pregnant women is necessary to supervise pregnant women in order to consume Fe tablets regularly. Because in this way, it can ensure the compliance of pregnant women to consume Fe tablets according to the predetermined dose and schedule (Ministry of Health, Republic of Indonesia, 2017). By developing a website-based application model that can be used as communication advice anytime and anywhere to monitor pregnant women to consume Fe tablets regularly. The purpose of this activity is to improve understanding of the use of the Sumiferos application. This community service activity uses the extension method with lectures, demonstrations, and question and answer methods. The results obtained from this activity are that pregnant women can use the Sumiferos application properly. The results of this community service are very important because the officers will monitor them through the Sumiferos application. The conclusion of this community service is that pregnant women are able to use the Sumiferos application properly and the compliance of pregnant women in consuming iron tanlets has increased